como resolver esta equação?
(x-3).4+1=65
muriloct:
4x-12+1=65
Soluções para a tarefa
Respondido por
15
fica assim:
![(x-3).4+1=65 (x-3).4+1=65](https://tex.z-dn.net/?f=%28x-3%29.4%2B1%3D65)
![4x-3.4+1=65 4x-3.4+1=65](https://tex.z-dn.net/?f=4x-3.4%2B1%3D65)
![4x-12+1=65 4x-12+1=65](https://tex.z-dn.net/?f=4x-12%2B1%3D65)
![4x-11=65
4x-11=65](https://tex.z-dn.net/?f=4x-11%3D65%0A)
![4x=65+11 4x=65+11](https://tex.z-dn.net/?f=4x%3D65%2B11)
![4x=76
4x=76](https://tex.z-dn.net/?f=4x%3D76%0A)
![x= \frac{76}{4} x= \frac{76}{4}](https://tex.z-dn.net/?f=x%3D+%5Cfrac%7B76%7D%7B4%7D+)
![x=19 x=19](https://tex.z-dn.net/?f=x%3D19)
espero ter ajudado
espero ter ajudado
Respondido por
3
4.x-12+1 = 65
4.x = 65+12-1
x = 76/4
x = 19
4.x = 65+12-1
x = 76/4
x = 19
Perguntas interessantes